Ephemeral Art in Thai Contemporary Art - Suteerangkul, Paweena (Silpa Bhirasri (Journal of fine arts), 2018)
This qualitative research has two objectives: [1] to study the concepts, contents,materials and changes of ephemeral art in Thai contemporary art, and [2] to classify the ephemeral art in Thai contemporary art. Selected samples of this research include 16 ephemeral artworks created between 1987 and 2017. A research tool is an in-depth interview.Research findings are:1. The concepts, contents, materials and changes of the ephemeral art in Thai contemporary art conform harmoniously. Each individual artist would like to reflect his/her own idea and subject matter relating to the natural law of instability. The artist express their concept and explicit content by applying the insubstantial characteristic of objects and decaying process. 2. The ephemeral art in Thai contemporary art can be classified by considering the elements of the ephemeral art, such as, directive intention, materials, inherent vice, and time. There are 3 types of the ephemeral art which are [1] the ephemeral art activated by nature,[2] the ephemeral art activated by human, and [3] the ephemeral art activated by nature and human.